Fluid consistencies. Material relationality in human engagements with water. (26th November 2014) - Strang, Veronica
Abstract: Material things are not just passive recipients of human categories, meanings and values, nor mere subjects of human agency. Their particular characteristics and behaviours are formative of human–non-human relations. The common material properties of things, and the shared cognitive and phenomenological processes through which people interact with them, generate recurrent ideas and patterns of engagement in diverse cultural and historical contexts. Despite growing instrumentalism in human 'management' of the material world, and the emergence of new relational forms, these patterns persist.